Defences to homicide. - Victorian Law Reform Commission (Melbourne : Victorian Law Reform Commission, 2004)
"On 21 September 2001 the Attorney-General asked the Law Reform Commission to review and report on defences and partial defences to homicide. This Final Report is the result of three years work on the reference, which has included conducting background research, considering how the defences operate in practice in Victoria and other jurisdictions, and discussing options for reform as part of the consultation process."--p. xix.
Ch. 1. Background to report -- Ch. 2. Provocation -- Ch. 3. Self-defence, duress and necessity -- Ch. 4. Evidence of relationship and family violence -- Ch. 5. People with mentally impaired functioning who kill -- Ch. 6. Infanticide -- Ch. 7. Sentencing.
"The Final Report reflects the law as at 1 August 2004."--T.p. verso.
"Unless otherwise stated, all references to legislation in this Report are to Victorian Legislation."--T.p. verso.
Bibliography: p. 340-358.
Also available via the World Wide Web.
Keywords: Homicide -- Australia; Self-defense (Law) -- Australia; Provocation (Criminal law) -- Australia; Defence (Law); Homicide; Victoria; Proposed legislation; Case studies